2009
DOI: 10.1016/j.neuroimage.2009.03.085
|View full text |Cite
|
Sign up to set email alerts
|

Steady state and induced auditory gamma deficits in schizophrenia

Abstract: Steady state auditory evoked potential (SSAEPs) in the electroencephalogram (EEG) and magnetoencephalogram (MEG) have been reported to be reduced in schizophrenia, most consistently to frequencies in the gamma range (40 Hz and greater). The current study evaluated the specificity of this deficit over a broad range of stimulus frequencies and harmonics, the relationship between phase locking and signal power, and whether induced 40 Hz activity was also affected. SSAEPs to amplitude modulated tones from 5 to 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
131
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 33 publications
(60 reference statements)
15
131
0
Order By: Relevance
“…Interestingly, also in this testing paradigm, the response amplitude of single cells, in terms of relative change in mean firing rate, showed a significant decrease in Df(h15q13)/+ compared to wild‐type mice (Krishnan et al . 2009). However, while PCs in Df(h15q13)/+ mice displayed a clear reduction in mean firing rate during the steady‐state phase for the frequency interval tested (20–80 Hz), interneurones only showed a tendency towards reduced mean firing which did not quite reach significance (mean firing rate for PCs and FSIs in mutants was on average: 45.5% and 94.5% of those in wt mice; anova main effect of genotype, P  < 0.001, F  = 20.13 and P  = 0.0586, F  = 3.59 respectively; post hoc test showed a significant genotype difference for PCs for all frequencies except 20 Hz; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, also in this testing paradigm, the response amplitude of single cells, in terms of relative change in mean firing rate, showed a significant decrease in Df(h15q13)/+ compared to wild‐type mice (Krishnan et al . 2009). However, while PCs in Df(h15q13)/+ mice displayed a clear reduction in mean firing rate during the steady‐state phase for the frequency interval tested (20–80 Hz), interneurones only showed a tendency towards reduced mean firing which did not quite reach significance (mean firing rate for PCs and FSIs in mutants was on average: 45.5% and 94.5% of those in wt mice; anova main effect of genotype, P  < 0.001, F  = 20.13 and P  = 0.0586, F  = 3.59 respectively; post hoc test showed a significant genotype difference for PCs for all frequencies except 20 Hz; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormalities in auditory-evoked γ-oscillatory activity have been observed in schizophrenia as well as other neuropsychiatric disorders such as autism (3,7,10,(46)(47)(48). To test for disruptions in oscillatory activity during the evoked response in the Dys1 −/− mice, EEG trials were wavelet-transformed to extract instantaneous power and phase over all frequencies from θ to γ (4-100 Hz) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent clinical studies also show abnormal γ-band oscillations (30-100 Hz) as an endophenotype of the illness that is associated with reduced cognitive function (3-7). Work in animal models shows a prominent role of cortical inhibitory networks in generating γ-oscillations (8, 9), which in turn, supports the role of aberrant GABAergic inhibition as an important potential component of schizophrenia (4,7,10,11). The GABA-producing enzyme glutamic acid decarboxylase is dysregulated in schizophrenia, and postsynaptic GABA A receptors are dysregulated as well (4).…”
mentioning
confidence: 92%
“…Following the original and landmark observation that 40 Hz ASSR is specifically deficient in schizophrenia subjects (Kwon et al, 1999), numerous reports have broadly confirmed the finding (Brenner et al, 2003;Krishnan et al, 2009;Light et al, 2006;Spencer, 2011;Spencer et al, 2008;Vierling-Claassen et al, 2008), and extended it to first-degree relatives of schizophrenia subjects (Hong et al, 2004;Rass et al, 2012), suggesting that such a deficit may be a trait marker. However, it is pertinent to note that 40 Hz ASSR deficit is not specific to schizophrenia and extends to some neuropsychiatric conditions including bipolar disorder (Oda et al, 2012;Rass et al, 2010) and autism spectrum disorders (Rojas et al, 2011;Wilson et al, 2007).…”
Section: Introductionmentioning
confidence: 89%